Indic scripts based online form filling - A Usability Exploration - Krishna, Ashish; Prabhu, Girish; Bali, Kalika; Madhvanath, Sriganesh (In proceedings of 11th International Conference on Human-Computer Interaction -2005, Las Vegas, July 22-27, 2005, 2005)
Emerging Markets are very different from other developed markets in the diversity of the user needs, motivations and the business environment dynamics. The average citizen in the emerging markets, especially from the lower socio-economic segment, is not computer-savvy, and often only semi-literate. He or she is fluent in the local, and knows little or no English. Also, because of the poor penetration of computers in these markets, handwriting still plays a central role in all spheres of life – from transactions and record keeping in business, to personal communication. India provides an ideal testing ground for this research because of its multilingual milieu (18 official languages supported by 10 official scripts, hundreds of unofficial languages and many minor scripts). In this paper we report the findings of a usability test, which was carried out with handwriting recognition based interface developed in Tamil to find out the preferences and user experience of the target population with a novel input device. The accuracy of handwriting recognizers is seen as a factor in determining the acceptability of these interfaces, but the task context also has a heavy influence in the acceptability (Frankish, Hull & Morgan 1994). In this study we investigated subjective ratings based on the user- computer interaction and did in-depth interviews and found out the potential of these interfaces is also very much dependent on task context, interface controls and the editing tools it provides. Also we got an insight into the cross-cultural difference that is very typical in the Asian testing grounds.